(3GdJShjb GdMOjK (B:s (3eONd TGed (B/s - (3GdWGFj, MejOs; (3GdUejOYj, eMehO s ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2010)
(3eONd Gdi GdJShjb h GdHjFI GdJShjbjI , GdShb h GdShb GdeSJgOaI h Sdhc GdeSJgdc GdTQGFj, fXGe GdeYdheGJ GdJShjbjI h HMhK GdJShjb , GdfJLGJ h GdNOeGJ h GdJSYjQ h GdJhRjY h GdJQhjLh CNjQG GdJShjb GdGdcJQhfjs
Keywords: (3GdJShjbs; (3GdJShjb GdGdcJQhfjs